THE FUTURE OF DIGITAL MARKETING COMMUNICATION: STRATEGIES FOR ENGAGING THE MODERN CONSUMER - Khairifa, Feni (OPINI: Journal of Communication and Social Science, 2024)
This study aims to explore the trends and strategies of effective digital marketing communication in increasing modern consumer engagement. The method used in this study is the Systematic Literature Review (SLR), which includes the identification, selection, and analysis of relevant studies from various academic and industry sources using the PRISMA approach. The results of the study indicate that effective digital marketing communication strategies rely on three main pillars: data-driven personalization, omnichannel integration, and ethical engagement. The use of artificial intelligence (AI) and machine learning has enabled more personalized and predictive marketing experiences, increasing consumer engagement and loyalty. In addition, social media-based marketing and user-generated content have proven to be more effective than conventional advertising methods. However, challenges such as data privacy, digital fatigue, and algorithmic filtering are still major concerns for the digital marketing industry.